A Bipartite Obturator Artery with Multiple Pelvic Branching—A Gynecologic Approach - Jailenne I. Quiñones-Rodríguez; Alexandra N. Acevedo-Arroyo; Camille L. Santiago-Negrón; Lucia F. Garcés-Torres; Carlos Fonseca-Salgado (Diagnostics, 2022)
Background: The obturator artery (OA) often presents multiple anatomical variations. These can be an atypical origin, variable anastomosis, or abnormal course within the pelvis. Methods: This study aimed to report a rare arterial variation in a Puerto Rican female cadaver that showed two abnormal obturator arteries with multiple pelvic branches. The OA emerged from the anterior branch of the internal iliac artery, which typically runs anteroinferior along the lateral wall of the pelvis to the upper part of the obturator foramen. Results: The atypical OA described in this report provided two variant branches. Abnormal obturator artery I (AOAI) emerged first and gave rise to three additional branches, while abnormal obturator artery II (AOAII) emerged second and gave rise to two other branches. Conclusions: Identifying these accessory arteries is essential for surgical interventions, particularly within the field of gynecology and urogynecology. Knowledge regarding anatomical variations within this region must be assessed preoperatively to decrease the risk of iatrogenic injury.